Megaloblastic erythropoiesis and macrocytosis in patients on anticonvulsants. Issue 5989 (18th October 1975) - Wickramasinghe, S N; Williams, G; Saunders, J; Durston, J H
Abstract : The results of deoxyuridine suppression tests on the bone marrow cells of 14 patients on anticonvulsant drugs, 11 of whom had evidence of megaloblastic erythropoiesis, indicated that the megaloblastic changes and macrocytosis encountered in treated epileptics are often not caused either by folate deficiency or by drug-induced impairment of the 5, 10-methylenetetrahydrofolate-dependent methylation of deoxyuridylate to thymidylate. A folate-related abnormality in the methylation of deoxyuridylate was found in only two of the 11 patients with megaloblastic erythropoiesis.